Examination of moisture sensitivity of aggregate–bitumen bonding strength using loose asphalt mixture and physico-chemical surface energy property tests - Liu, Yawen; Apeagyei, Alex K.; Ahmad, Naveed; Grenfell, James; Airey, Gordon (Taylor and Francis, 2014)
In this study, the moisture sensitivity of different kinds of aggregates and bituminous binders is examined by comparing the performance between five empirical test methods for loose mixtures – static immersion test, rolling bottle test (RBT), boiling water test (BWT), total water immersion test and the ultrasonic method – with more fundamental surface energy-based test data. The RBT and BWT results showed that limestone aggregates perform better than granite aggregates and that, for unmodified binders, stiffer binders provide better moisture resistance compared with softer binder. Both tests were sensitive to aggregate type, binder type and anti-stripping agent type. Ranking of the mixtures by RBT and BWT was in general agreement with the surface energy-based tests, especially for mixtures that performed worst or best in RBT and BWT. The magnitude of the work of debonding in the presence of water was found to be aggregate type dependent which suggests the physico-chemical properties of aggregates may play a fundamental and more significant role in the generation of moisture damage, than bitumen properties.